Implementasi (Planning Matrix) Perencanaan pada Anak Usia 4-5 Tahun dengan Gangguan Lambat Bicara: Implementation (Planning Matrix) Planning for 4-5 Year Old Children with Slow Speech Disorders - Erni Setiawati; Ervin Nurul Affrida (Universitas Ngudi Waluyo, 2024)
ABSTRACT This study aims to present a structured intervention plan for a 4-5 year old child with slow speech disorder. Improving the verbal communication skills of this child through targeted strategies is the main objective of this study. Specific objectives included an increase in vocabulary and improvements in the expression of the child's basic needs and feelings. The intervention plan involved a variety of strategies, such as speech and language activities, articulation exercises, and interactive games. Evaluation methods involved weekly progress monitoring and checklists to measure improvements in vocabulary and speech intelligibility. Utilization of resources, such as consultation with a speech therapist and age-appropriate speech therapy apps, is crucial. Parental involvement is strongly encouraged by providing guidance to parents to help strengthen communication at home. Program adjustments are made based on monthly evaluations and feedback from parents. The continuation plan involves regular meetings with parents to monitor progress and discuss next steps that may be needed. This research offers a comprehensive and customizable approach, emphasizing strategies that are specific to a child's unique needs and development. The results of this study show deep insight into the experiences of 4-5 year old children with slow speech impairment who received the implementation of the intervention plan and brought significant positive impacts ABSTRAK Penelitian ini bertujuan untuk menyajikan suatu rencana intervensi terstruktur bagi anak usia 4-5 tahun yang mengalami gangguan lambat bicara. Meningkatkan keterampilan komunikasi verbal pada anak ini melalui strategi yang ditargetkan merupakan tujuan utama dalam penelitian ini. Untuk tujuan khusus mencakup peningkatan kosakata dan perbaikan dalam ekspresi kebutuhan dasar dan perasaan anak. Rencana intervensi melibatkan beragam strategi, seperti kegiatan bicara dan bahasa, latihan artikulasi, dan permainan interaktif. Metode evaluasi melibatkan pemantauan kemajuan mingguan dan checklist untuk mengukur peningkatan kosakata dan kejelasan bicara. Pemanfaatan sumber daya, seperti konsultasi dengan terapis bicara dan aplikasi terapi bicara yang sesuai dengan usia, menjadi krusial. Keterlibatan orang tua sangat dianjurkan dengan memberikan panduan kepada orang tua untuk membantu memperkuat komunikasi di rumah. Penyesuaian program dilakukan berdasarkan evaluasi bulanan dan umpan balik dari orang tua. Penelitian ini merupakan pendekatan yang komprehensif dan dapat disesuaikan, menekankan strategi yang spesifik untuk kebutuhan dan perkembangan unik anak. Hasil penelitian ini menunjukkan wawasan yang mendalam tentang pengalaman anak usia 4-5 tahun dengan gangguan lambat bicara yang menerima implementasi perencanaan intervensi dan membawa dampak positif yang signifikan.